Assessment of the domestic marketing system of grapes in Nashik district, Maharashtra, India - Pagar, Deven Lalaji; Kuwornu, John K. M.; Bhujel, Ram C.; Tsusaka, Takuji W.; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2019)
Grapes are considered as the one of the most important and leading crops in Nashik district of Maharashtra state in India. Therefore, the present study was conducted in Nashik district to understand the different marketing channel system, various supply chain actors working in the system and problem faced by the farmers and trader in the domestic market of grape. General objective of this research was to assess domestic marketing system of grape. The specific objective of this study is: 1) To map supply chain actors of grapes in the study area. 2) To examine the factors influencing producers{u2019} choice of marketing channel of grapes in the study area. 3) To identify constraints of producers{u2019} and actors of marketing system of grape industry in the study area. The surveyed questionnaire was used to interview 120 grape farmers and 70 traders of grape marketing system. The descriptive statistic was use to present the demographical information of respondent. The Generic worksheet crossing functions was used to identify the actors present in grapes subsector in study area. The bivariate probit regression model and binary probit model were used to identify the factors influencing choice of market channel by the farmers. In Addition, Garret ranking method was used to identify the constraints of producers and actors of grape marketing system in study area. Results from the study revealed that the average age of the grape growers was about 42 years and their main occupation was agriculture. It could be further observed that majority of the respondents were literate (99.2%), with their educational level ranging from primary to degree level. The remaining 0.8 percent of growers were illiterates. Traders main occupation was either local trader or wholesaler. The further observed that all of the trader respondents were literate (100%), with their educational level ranging from high school to degree level. The key actors participating in supply chain process in study area was input supplier, producer, wholesaler/ local trader, processor, retailer and consumer with supporting actors. There are two types of marketing channel operating in Nashik district, India: Wholesaler channel (Producer {u2013} Wholesaler- Retailer- Consumer). Another type of market channel is the Local market, which is operated as producer- local market {u2013} retailer- consumer. For the wholesaler market channel, farm size, income, production and contract agreement positively influenced the farmers{u2019} decision to choose of wholesaler market channel, whereas age negatively influenced farmers{u2019} decision to choose the wholesaler market channel system. Now in terms local market channel, age significantly influence the farmers{u2019} choice of marketing channel, whereas farm size, income, production and contract agreement negatively influence the decision of farmers to use the local market channel in grape market system. From the discussions with the sample farmers it was found that most of the farmers faced several marketing problems like delayed payment, fluctuation in market price, at third level high cost of transportation, low yield, low selling price. Major challenges faced in the marketing of grape by traders the major challenges were the long-time payment, Poor co ordination in the marketing channel, the low selling price, High cost Storage fee.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Agribusiness Management
Thesis (M. Am.) - Asian Institute of Technology, 2019
Keywords: Markets -- India; Business logistics -- India; Grapes -- India